Aspek Pendengaran, Penglihatan dan Perenungan Sebagai Elemen Asas Pemikiran Kritis Menurut Perspektif al-Qur’an - Kadri, Zainoriah; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2012)
This article discusses the three main aspects that constitute the most basic element of critical thinking from the Qur’anic perspective. It involves a synthesis of listening, seeing and contemplating. The Qur’anic terms related to these aspects will be discussed in this article. The Qur’anic terms in the category of listening are words of سَمْع (sam‘) and أُذن (udhun). While in the category of seeing, the keywords are نَظَر (nazar),رَاَئ (raa), بَصَر (basar), شَهَادَة (syahadah), عَين (‘ayn) and طَرْف(tarf). Keywords in the contemplating category includeوَعَى (wa‘a), قَلْب (qalb) and فُؤَاد (fu’ad). Content analysis is done on each keyword and its background information is determined: its root word, meaning, number of usage, derivative forms, location, whether it is a verb or a noun. If it is a verb: what tense it is, whether it is in the past, present/future, imperative (command) or prohibitive; whether it is located in a Makki or Madani sura, whether it is in the form of singular, dual or plural; and its Quranic meanings. The three main aspects which synthesize hearing, seeing and contemplating, become the basic method in the formation and development of the Qur’anic critical thinking concept. It is also an important method in finding the truth, hence recognizing Allah SWT as the Only God worthy of worship.